Tính a) √(4-2√3).(13+4√3) b) ( √3-2).( √6+ √2). √√3+2 c) (3+ √5).( √10 – √2). √3- √5 d) (4+ √15).( √10- √6). √4- √15 Giúp mk với cảm ơn nhiều mk sẽ

Question

Tính
a) √(4-2√3).(13+4√3)
b) ( √3-2).( √6+ √2). √√3+2
c) (3+ √5).( √10 – √2). √3- √5
d) (4+ √15).( √10- √6). √4- √15
Giúp mk với cảm ơn nhiều mk sẽ tick cho

in progress 0
Reagan 1 tuần 2021-09-02T13:00:02+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-09-02T13:01:17+00:00

    Bn xem hình

    0
    2021-09-02T13:01:40+00:00

    $a) \sqrt{4-2\sqrt{3}}.(13+4\sqrt{3})\\=\sqrt{(1-\sqrt{3})^{2}}.(13+4\sqrt{3})\\=(\sqrt{3}-1).(13+4\sqrt{3})\\=13\sqrt{3}+12-13-4\sqrt{3}\\=9\sqrt{3}-1\\b) (\sqrt{3}-2)(\sqrt{6}+\sqrt{2})\sqrt{\sqrt{3}+2}
    \\=(\sqrt{18}+\sqrt{6}-2\sqrt{6}-2\sqrt{2})\sqrt{\sqrt{3}+2}\\=(3\sqrt{2}+\sqrt{6}-2\sqrt{6}-2\sqrt{2})\sqrt{\sqrt{3}+2}\\=(\sqrt{2}-\sqrt{6})\sqrt{\sqrt{3}+2}\\=\sqrt{2(\sqrt{3+2})}-\sqrt{6(\sqrt{3}+2)}\\=\sqrt{2\sqrt{3}+4}-\sqrt{6\sqrt{3}+12}\\=\sqrt{(1+\sqrt{3})^{2}}-\sqrt{(3+\sqrt{3})^{2}}\\=1+^{3}-(3+^{3})\\=1+\sqrt{3}-3-\sqrt{3}\\=-2\\c) (3+\sqrt{5}).(\sqrt{10}-\sqrt{2})\sqrt{3}-\sqrt{5}\\=(3.\sqrt{3}+\sqrt{15})(\sqrt{10}-\sqrt{2})-\sqrt{5}\\=3\sqrt{30}-3\sqrt{6}+\sqrt{150}-\sqrt{30}-\sqrt{5}\\=3\sqrt{30}-3\sqrt{6}+5\sqrt{6}-\sqrt{30}-\sqrt{5}\\=2\sqrt{30}+2\sqrt{6}-\sqrt{5}\\d) (4+\sqrt{15})(\sqrt{10}-\sqrt{6})\sqrt{4}-\sqrt{15}\\=(4+\sqrt{15})(\sqrt{10}-\sqrt{6}).2-\sqrt{15}\\=(8+2\sqrt{15})(\sqrt{10}-\sqrt{6})-\sqrt{15}\\=8\sqrt{10}-8\sqrt{6}+2\sqrt{150}-2\sqrt{90}-\sqrt{15}\\=8\sqrt{10}-8\sqrt{6}+10\sqrt{6}-6\sqrt{10}-\sqrt{15}\\=2\sqrt{10}+2\sqrt{6}-\sqrt{15}$

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )